Idealisme Seniman Berdampak pada Marginalisasi Kesenian Indang Tradisi - Indrayuda Indrayuda (Institut Seni Indonesia Yogyakarta, 2019)
This article aims to reveal and analyze the problem of the artistry of traditional art in Padang Pariaman district. Today the existence of Indang art less popular in the cultural life of the community Padang Pariaman. In turn, Indang art is rarely used and functioned by Padang Pariaman society today. The research was done by explanation method, and the research data is qualitative. Data collected throughout the interview process, observation of socio-cultural symptoms of society, and the existence of Indang. The analysis was done by ethnography approach, by determining component analysis and determining the cultural theme. The result of the research obtained is that the structure and shape of Indang have not changed until now. Indang art form and structure is less suitable to the taste of today’s society so that Indang art is less popular to the public for entertainment activities. The activities of artists on stage often disturb the artistic and aesthetic performances, i.e. the artists often create any activities that spoil the atmosphere of the show.Keywords: Indang tradisi; form and structure; ethnographic approach; explanation method